ASMARADANA: DI AMBANG LIMINAL - Sunahrowi Sunahrowi (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Asmaradana short story has one face, but exists on two worlds. In one side, it show postmodern world and on the other sideshow its feminism thread. This short story justified being had one face because between postmodernism and feminism offer critic that deepand extensive reach to philosophy and its correlation with broaden culture. Both try to develop new paradigm of social critic, which not basedon traditional philosophical basis. This short story exists on two worlds because postmodernism community offers complex and complicatedcritics to foundationalism and essentialism. However, their social critic’s conception tends to have weak power. The existence of Asmaradanashort story between postmodernism and feminism theme making this short story have liminal character